ANALISIS MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Syamsul Ma'arif Al fatah; Jupriyanto Jupriyanto; Andarini Permata Cahyaningtyas (Jurnal Pesona Dasar, 2019)
This research is focused on the analysis media of interactive multimedia learning which is used in the learning process in elementary schools towards the learning motivation of students. Education becomes an important thing in everyday life. In education a lot of potential exists in a person to be developed optimally. In the education process, not only prioritizing the improvement of academic abilities, because education also requires cultural transformation, education can also be made as a long-term investment. Furthermore, at this time, it is still minimum, the reading interest index in Indonesia, based on the study of "The Most Scattered Nation in the World" conducted by Central Connecticut State University in March 2016, Indonesia used the 60th rank out of 61 countries in the world regarding reading interest . Indonesia is under Thailand (59) and right above Bostwana (61). Current technological advances require the use of interactive multimedia learning media that need to be improved. Interactive multimedia media has a unique design, so that the motivation of students can be intrigued, interactive multimedia with an attractive design can lead to great motivation towards students, able to make the learning process more focused.